Decis\~oes críticas em idades críticas: A escolha dos jovens entre estudo e trabalho no Brasil e em outros países da América Latina - Carlos Henrique Corseuil; Daniel Domingues dos Santos; Miguel Nathan Foguel (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
In this paper we pretend to compare the determinants of the time allocation of the teenagers among four Latin American countries: Brazil, Chile, Peru and Honduras. We assume there are four possibilities to time allocation: only studying, only working, doing both of them or doing none of them. We focused our attention in Brazil, reporting how far one can extend the conclusions and policy recommendations to the another countries with different social and geographical characteristics. Separate analysis were done for men and women. The specific impacts of each variable on the time allocation of the teenagers were compared through a graphic analysis. The parents education revealed being the most important determinant of the young people's choice in almost all countries and genders analyzed, in the sense that the more educated the parents are, the more likely to study and the less willing to work the children are. In Brazil, for example, sons/daughters of eight-year educated parents have probability of studying 17/14 percentage points lower than sons/daughters of analphabets. Other important variables were the household location and the family composition, however the direction of these impacts depended on the gender and the country considered. This fact supports the argument that institutional/cultural differences have a central role on the teenagers' time allocationIn this paper we pretend to compare the determinants of the time allocation of the teenagers among four Latin American countries: Brazil, Chile, Peru and Honduras. We assume there are four possibilities to time allocation: only studying, only working, doing both of them or doing none of them. We focused our attention in Brazil, reporting how far one can extend the conclusions and policy recommendations to the another countries with different social and geographical characteristics. Separate analysis were done for men and women. The specific impacts of each variable on the time allocation of the teenagers were compared through a graphic analysis. The parents education revealed being the most important determinant of the young people's choice in almost all countries and genders analyzed, in the sense that the more educated the parents are, the more likely to study and the less willing to work the children are. In Brazil, for example, sons/daughters of eight-year educated parents have probability of studying 17/14 percentage points lower than sons/daughters of analphabets. Other important variables were the household location and the family composition, however the direction of these impacts depended on the gender and the country considered. This fact supports the argument that institutional/cultural differences have a central role on the teenagers' time allocation.
Keywords: 330; Zeitverwendung; Jugendliche; Brasilien; Chile; Peru; Honduras